2021
DOI: 10.12788/jhm.3660
|View full text |Cite
|
Sign up to set email alerts
|

Continuing Cardiopulmonary Symptoms, Disability, and Financial Toxicity 1 Month After Hospitalization for Third‐Wave COVID‐19: Early Results From a US Nationwide Cohort

Abstract: BACKGROUND: Patients discharged after COVID-19 report ongoing needs. OBJECTIVES: To measure incident symptoms after COVID-19 hospitalization. DESIGN, SETTING, AND PARTICIPANTS: Preplanned early look at 1-month follow-up surveys from patients hospitalized August 2020 to January 2021 in NHLBI PETAL Network’s Biology and Longitudinal Epidemiology: COVID-19 Observational (BLUE CORAL) study. English- or Spanish-speaking hospitalized adults without substantial pre-COVID-19 disability with a positive molecular test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 45 publications
2
28
1
Order By: Relevance
“…Moreover, the mean physical function score was less than one standard deviation below normal. In contrast to other studies, [7][8][9][10][11] we found evidence for debilitating physical and mental disability in only a small portion of our patient sample. The PROPr score was 0.46 (SD 0.3), which is worse than the mean PROPr score (0.52) observed in the US population; 44,50 however, this difference is less than the effect of chronic illness on PROPr (ie, emphysema 50 and dialysis 51 decrease PROPr by about −0.2).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover, the mean physical function score was less than one standard deviation below normal. In contrast to other studies, [7][8][9][10][11] we found evidence for debilitating physical and mental disability in only a small portion of our patient sample. The PROPr score was 0.46 (SD 0.3), which is worse than the mean PROPr score (0.52) observed in the US population; 44,50 however, this difference is less than the effect of chronic illness on PROPr (ie, emphysema 50 and dialysis 51 decrease PROPr by about −0.2).…”
Section: Discussioncontrasting
confidence: 99%
“…1 While the acute phase of the illness has been well described, [2][3][4][5][6] the post-discharge outcomes of patients who were critically ill from COVID-19 has not been well-reported, particularly in the United States (U.S.). [7][8][9][10][11][12] As such, we sought to describe long-term outcomes of patients who required admission to an intensive care unit (ICU).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, studies of hospitalized COVID patients report longer‐term impairments often with new disabilities despite normal function at baseline. 8 These factors may impact a provider's clinical decision‐making surrounding referral to PT and/or OT as well as rehabilitation therapist's decisions on which patients to evaluate and/or treat at the bedside. Physical therapists and occupational therapists within acute care hospitals are often consulted to assist with discharge planning, especially for patients who may require placement and/or postacute care rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 , 5 Patients hospitalized for novel coronavirus (COVID‐19) infection experience fatigue, myalgias, respiratory symptoms, impaired physical function, and cognitive deficits, 6 , 7 and they are at high risk for new disability, with more than half reporting new disability and/or functional challenges at 1 month post hospitalization. 8 Increasing illness severity, especially amongst patients requiring mechanical ventilation, is associated with a greater likelihood of posthospital morbidity. 3 Thus, it is likely that many patients will develop significant deficits requiring rehabilitation during, and following, hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…79 Consequently, loss of income is common, reported in 71% of ICU survivors in the year following critical illness, 86 as are other elements of financial toxicity, such as loss of health care coverage, depletion of savings, and medical bills. [86][87][88] Family structure and roles may be also altered, as one-quarter of ICU survivors report needing a caregiver 1 year after critical illness. The vast majority of care is provided by family members, half of whom report a resultant negative impact on employment.…”
Section: Social and Financial Considerationsmentioning
confidence: 99%